Lao People's Democratic Republic : Staff Report for the 2002 Article IV Consultation and Second Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines Lao People's Democratic Republic's (Lao PDR) 2002 Article IV Consultation, Second Review Under the Poverty Reduction and Growth Facility (PRGF), and a Request for Waiver of Performance Criteria. Over the past 15 months, Lao PDR has made substantial progress under the PRGF-supported program. Program implementation has been effective, and the program remains broadly on track. All quantitative performance criteria were met except for the net domestic assets of the state commercial banks. On the macroeconomic side, the program for 2002-03 consolidates stabilization efforts.